1993
DOI: 10.1007/bf01956145
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of complement activation in premature newborn infants with hyaline membrane disease

Abstract: Fifteen premature newborns with hyaline membrane disease causing acute respiratory distress were evaluated for complement activation. A high intrapulmonary right-to-left shunt and marked arterial-alveolar oxygen difference indicated the severity of the respiratory failure. Twenty preterm healthy infants served as controls. Total haemolytic activity, plasma concentrations of complement components and regulatory proteins (C3, C4, C1-inhibitor, factors H and I) as well as activation products (C3a, C3dg, C1rsC1-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 29 publications
0
12
2
Order By: Relevance
“…Davis et al (1979) also indicated that these levels were still lower than adult levels at 6 months after birth. These fH and fI levels were not substantially lower in the 27-37 week gestation preterm neonates reported by Cat et al (1993), than the levels in term neonates.…”
Section: Concentrations Of Serum Complement Regulatorscontrasting
confidence: 68%
See 3 more Smart Citations
“…Davis et al (1979) also indicated that these levels were still lower than adult levels at 6 months after birth. These fH and fI levels were not substantially lower in the 27-37 week gestation preterm neonates reported by Cat et al (1993), than the levels in term neonates.…”
Section: Concentrations Of Serum Complement Regulatorscontrasting
confidence: 68%
“…levels and that the C1 inhibitor levels were reduced, rather than elevated, in the mothers relative to non-pregnant controls. Cat et al (1993) subsequently studied C1 inhibitor levels in preterm infants and reported a mean of 17.5 ± 6.0 U/ml functional titre but only indicated that relative to the control adult serum values the range was 42-84%. Relative to adult serum, C4BP levels in normal term neonates is very low and in some studies lower than the threshold of detection (de Paula et al 2003).…”
Section: Concentrations Of Serum Complement Regulatorsmentioning
confidence: 95%
See 2 more Smart Citations
“…C1rs‐C1Inh and C3b(Bb)P. Specific activation of the classical and alternative pathways was analysed by measuring the protein–protein complexes C1rs‐C1inhibitor (C1rs‐C1Inh) and C3b(Bb)P, respectively, by ELISA, basically as described in Cat et al 1993 [20]. Briefly, microtitre plates (Nunc) were coated with rabbit antiC1Inh IgG (Dakopatts) or goat antiproperdin IgG (Baxter, Unterschleisheim, Germany).…”
Section: Methodsmentioning
confidence: 99%